Time thief - Keene, Carolyn (Keene, Carolyn. Nancy Drew and the clue crew, 2011)
Nancy and her friends watch the principal dig up the school's time capsule, buried over thirty years ago, but when an important vintage doll is discovered missing from the capsule, the Clue Crew is called in to investigate.